MODERN INFRASTRUCTURE FOR MODERN POLICING: GUJARAT POLICE HOUSING CORPORATION - Rajput Thanabhai Varajangabhai (International Educational Journal of Science and Engineering, 2026)
The effectiveness of the modern policing is well increasingly determined not only by manpower strength and technological capability, but also by the quality, availability, as well as governance of supporting infrastructure. Residential housing is another crucial attribute that has been underexplored among the other factors in police infrastructure. Adequacy of the housing of the police directly affects the readiness of the operations, the response rate, morale, staff retention, and institutional stability (Kumar et al., 2024). The current research paper is a discussion of the analysis of a Gujarat State Police Housing Corporation Limited including the history of its formation since 1988 to the current stage of the maximum intensity of the infrastructure development up to 2025-26 and beyond. The article will possess a longitudinal analytical paradigm that implies the investigation of why the Corporation was founded and the evolution of roles at various time periods, the adaptation of the design and cost organizations to the pressure of the city, and the reworking of the assumptions of the housing policy based on the demands of the recruitment (Gupta et al., 2022). The paper is anchored on the official reports on the annual reports and reports on the infrastructure analysis by claiming that the police housing in Gujarat was no longer a numeral issue of inadequacy but a problem of governance of difficulty. This is to be handled through undertaking proactive planning, institutional capacity building, design thinking and lifecycle and synergies between the housing policy and recruitment and urban development policy.